Religion as a context for language contact - Nesher, Elinor (Journal of Religion and Linguistics, 2025)
Even though there is a lot of research on religious language, not much research has been done on how language and religion interact when someone is bilingual or multilingual until recently. This chapter initially presents a summary of prior research, predominantly focused on the translation of sacred writings into diverse languages. Some research has already looked into how the spread of religion has affected language, especially when it comes to choosing ceremonial language and writing systems. We examine the linguistic patterns and practices traditionally associated with several religious traditions, including Buddhism, Christianity, Hinduism, Islam, Judaism, and Quakerism. After that, the chapter talks about the language effects of missionary work in different postcolonial settings, mainly those that have to do with Christian groups. Recent studies have investigated the linguistic effects of connections between regionally dominant languages and dialects and religious practices in various global contexts. The researcher also examines the interplay between immigration and the preservation or alteration of language within religious contexts. The chapter concludes by observing that recent political developments, interest in conversion initiatives for non-Christian religions, and an increasing acknowledgment of the academic validity of language and religion forecast a probable rise in applied linguistic study in this domain.